Volume 5: Education and Globalization 2014
DOI: 10.1115/imece2014-38698
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes for Low Student Office Hour Attendance

Abstract: It is long understood that many students do not take advantage of faculty assistance outside of class. In an attempt to improve the use of office hours, faculty have made efforts to schedule times that are most convenient to students and are most likely to have high attendance; before homework assignments are due or examinations are being held. Despite these efforts, students rarely take advantage of this support service. As a first attempt to improve student engagement, the number of office hours held by teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Online education's ability to let students of different backgrounds and disciplines learn together can amplify the benefits of social learning 13 in a way rarely captured in pre-pandemic education. We need to rethink social interactions to be inclusive and flexible, and no longer restrict them to educator and learner; traditional 'office hours' are already poorly attended and less effective 14,15 . Instead, a post-pandemic learning environment should broaden learner-learner interactions across degrees, universities, workplace and K-12 experiences.…”
Section: Social Learningmentioning
confidence: 99%
“…Online education's ability to let students of different backgrounds and disciplines learn together can amplify the benefits of social learning 13 in a way rarely captured in pre-pandemic education. We need to rethink social interactions to be inclusive and flexible, and no longer restrict them to educator and learner; traditional 'office hours' are already poorly attended and less effective 14,15 . Instead, a post-pandemic learning environment should broaden learner-learner interactions across degrees, universities, workplace and K-12 experiences.…”
Section: Social Learningmentioning
confidence: 99%
“…A study conducted at Russian universities reported that few students took advantage of professors' office hours to come and discuss research and professional questions: 18% of surveyed undergraduates discussed course concepts or ideas with their professors and only 6% talked about career plans (Chirikov, 2015), which indicates that students are unlikely to benefit from the opportunity to communicate with academic staff. In American and Australian universities, for example, attendance at office hours has also appeared infrequent (Briody et al, 2019;Robinson et al, 2014).…”
Section: Students In Transition and Education Trends: Case Study Observationsmentioning
confidence: 99%
“…For example, past work has been limited to single courses or a closely linked series of courses, primarily in R1 universities and within engineering ( Griffin et al. , 2014 ; Robinson et al. , 2015 ; Smith et al.…”
Section: Introductionmentioning
confidence: 99%